2017
DOI: 10.1097/gme.0000000000000769
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of midlife women by physical activity and their racial/ethnic differences

Abstract: Objective The purpose of this study was to identify clusters of midlife women by physical activity and to determine racial/ethnic differences in physical activities in each cluster. Methods This was a secondary analysis of the data from 542 women (157 Non-Hispanic [NH] Whites, 127 Hispanics, 135 NH African Americans, and 123 NH Asian) in a larger Internet study on midlife women’s attitudes toward physical activity. The instruments included the Barriers to Health Activities Scale, the Physical Activity Assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…This is a large and diverse group that has high healthcare utilization and costs (22), despite prevention and intervention efforts to lower their health risks. Existing evidence indicates that midlife women's cardioprotective behaviors, such as physical activity engagement and dietary choices, are influenced by their perceptions of their social environments [e.g., social support for healthy behavior, negative judgments from others (23)(24)(25)]. As both social perceptions and health behaviors vary within and across days, weeks, and months, as well as between people (26)(27)(28)(29), intensive assessments could be crucial for understanding at what level(s) these processes are associated among midlife women.…”
Section: Case Example: Intensive Assessment Among Midlife Women With Elevated Risk For Cardiovascular Disease (Cvd)mentioning
confidence: 99%
“…This is a large and diverse group that has high healthcare utilization and costs (22), despite prevention and intervention efforts to lower their health risks. Existing evidence indicates that midlife women's cardioprotective behaviors, such as physical activity engagement and dietary choices, are influenced by their perceptions of their social environments [e.g., social support for healthy behavior, negative judgments from others (23)(24)(25)]. As both social perceptions and health behaviors vary within and across days, weeks, and months, as well as between people (26)(27)(28)(29), intensive assessments could be crucial for understanding at what level(s) these processes are associated among midlife women.…”
Section: Case Example: Intensive Assessment Among Midlife Women With Elevated Risk For Cardiovascular Disease (Cvd)mentioning
confidence: 99%
“…21 However, little is known about the patterns of physical activity for women during midlife. 22 Many adults worldwide do not engage in sufficient levels of physical activity. One British study reported that 38% of women aged 45 to 54 years did not achieve the recommended guidelines, and 30% of those who exercised stated that they became "less [physically] active" during menopause.…”
mentioning
confidence: 99%
“…By considering multiple factors that influence physical activity, researchers and practitioners can better inform the development of physical activity programs for women during menopause transition and midlife. 22 This systematic review is the first to use a socioecological perspective to investigate the barriers and enabling factors influencing engagement in physical activity by women during the phases of menopause. Understanding these factors will guide the development of interventions and tailor strategies toward increasing women's physical activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with several theories of health behavior, including social-cognitive theory (Bandura, 1998 ) and Midlife Women’s Attitudes Toward Physical Activity Theory (MAPA; Im et al, 2010 ), perceptions of the social environment are key to PA engagement in this group. For example, more (vs. less) positive perceptions of social norms for PA are associated with greater PA engagement among women in midlife (Im et al, 2011 , 2017 ; Janssen et al, 2014 ). Social comparisons , or self-evaluations relative to others (Festinger, 1954 ) represent a specific set of social perceptions that may have similar influences on midlife women’s PA, but these relations have received little attention.…”
mentioning
confidence: 99%